Atmospheric nitrogen dioxide at different concentrations levels regulates growth and photosynthesis of tobacco plants. Issue 1 (1st January 2021) - Jiechen, Wang; Yue, Wang; Huihui, Zhang; Dandan, Guo; Guangyu, Sun
ABSTRACT: Nitrogen dioxide (NO2 ) is recognized as a toxic gaseous pollutant. However, an appropriate concentration of NO2 can promote the growth of plants. In this study, tobacco was exposed to different concentrations of NO2 . The results that 1, 4, and 8 μL L −1 NO2 fumigation increased the net photosynthetic rate ( P n ), maximum photochemical efficiency ( F v / F m ) and light energy utilization capacity parameters ( PI ABS ) of leaves, and promoted the growth of seedlings. About 16 μL L −1 NO2 caused the leaves to wither, and the plants were about to die after five days of fumigation. About 8 μL L −1 NO2 obviously promoted the growth of plants, but meanwhile, the old leaves began to show signs of damage, such as bruising and yellowing. Therefore, 8 μL L −1 may be the threshold concentration of herbaceous plants with high NO2 assimilation ability. At an intermediate concentration (4 μL L −1 ) within the threshold range, NO2 is most beneficial to the growth of herbaceous plants.